Pengaruh Permainan Tradisional Berbasis Kelompok dan Berbasis Individu Ditinjau dari Jenis Kelamin Terhadap Kemampuan Gerak Dasar pada Siswa Kelas 5 - Suparsih, Suparsih (Jurnal Simki Postgraduate, 2023)
This study aims to determine: (1) Differences in the effect of group-based and individual-based traditional games on improving basic motor skills in students. (2) Differences in the effect of increasing basic movement skills in students who have male and female gender in improving students' basic movement skills. (3) The effect of interaction between traditional games and gender on students' basic motor skills. The research was conducted at SDN Puhsarang 1 Kediri in the 2015/2016 academic year. The size of the research sample is 22 students from the entire population. Sampling technique with purposive random sampling. The research variables consisted of two independent variables, namely: manipulative variables: group-based and individual-based traditional games, attributive variables namely: male and female sex and the dependent variable namely: tests of students' basic movement abilities. Data collection techniques were tests and measurements, gender grouping tests, data on students' basic movement ability tests with hand-eye coordination basic ability tests, 30 meter running, shuttle run and stork stand tests. The data analysis technique used ANOVA 2x2 analysis of variance with a significance level of  = 0.05. Based on the results of the study it can be concluded: 1) There is an influence between the treatment of group and individual-based traditional game skills on basic movement abilities in grade 5 students at SDN Puhsarang 1 Kediri Regency in the 2015/2016 Academic Year. 2) There is an influence on the results of basic motor skills between students who have male and female gender in grade 5 students at SDN Puhsarang 1, Kediri Regency, 2015/2016 Academic Year. 3) There is an interaction between the treatment of traditional games and gender on the results of basic motor skills in grade 5 students at SDN Puhsarang 1 Kediri Regency in the 2015/2016 Academic Year.